2020
DOI: 10.1186/s12891-020-03479-9
|View full text |Cite|
|
Sign up to set email alerts
|

Bilobalide protects against ischemia/reperfusion-induced oxidative stress and inflammatory responses via the MAPK/NF-κB pathways in rats

Abstract: Background Clinically, skeletal muscle ischemia/reperfusion injury is a life-threatening syndrome that is often caused by skeletal muscle damage and is characterized by oxidative stress and inflammatory responses. Bilobalide has been found to have antioxidative and anti-inflammatory effects. However, it is unclear whether bilobalide can protect skeletal muscle from ischemia/reperfusion injury. Methods The effects of bilobalide on ischemia/reperfusion-injured skeletal muscle were investigated by performing he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 41 publications
(60 reference statements)
0
18
0
Order By: Relevance
“…Several studies in human models have demonstrated that quadriceps muscle atrophy after TKA can be more affected by stress responses to tourniquet-induced IR injury than surgical trauma [ 6 , 7 ]. IR injury is often accompanied by oxidative stress (ROS overproduction and inactive antioxidative stress-related proteins) and inflammatory responses (pro-inflammatory cytokine expression and inflammatory cell infiltration) [ 8 , 9 , 10 ]. During IR injury, excessive production of ROS and pro-inflammatory cytokines play important roles in the infiltration of inflammatory cells (leukocytes) into tissues subjected to ischemia and reperfusion, which is characterized by the activation of leukocytes, leukocyte–endothelial cell adhesion, and transmigration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies in human models have demonstrated that quadriceps muscle atrophy after TKA can be more affected by stress responses to tourniquet-induced IR injury than surgical trauma [ 6 , 7 ]. IR injury is often accompanied by oxidative stress (ROS overproduction and inactive antioxidative stress-related proteins) and inflammatory responses (pro-inflammatory cytokine expression and inflammatory cell infiltration) [ 8 , 9 , 10 ]. During IR injury, excessive production of ROS and pro-inflammatory cytokines play important roles in the infiltration of inflammatory cells (leukocytes) into tissues subjected to ischemia and reperfusion, which is characterized by the activation of leukocytes, leukocyte–endothelial cell adhesion, and transmigration.…”
Section: Discussionmentioning
confidence: 99%
“…A tourniquet is used during TKA to produce a bloodless surgical field. However, tourniquet use also induces IR injury, which is often accompanied by oxidative stress (overproduction of inactive antioxidative stress-related proteins and reactive oxygen species—ROS) and inflammatory responses (pro-inflammatory cytokine expression and inflammatory cell infiltration), causing damage to tissues subjected to ischemia and reperfusion [ 8 , 9 , 10 ]. Some studies have demonstrated that tourniquet-induced IR injury alters muscle protein metabolism, including a reduction in protein synthesis [ 11 ], increase in protein degradation [ 7 ], and upregulation of genes involved in cell stress pathways [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…These effects indicated that BB could effectively alleviate ischemia–reperfusion injury of skeletal muscle cells (Ying Li, 2020). Meanwhile, Li et al (2020) also proved that BB can protect hind limb skeletal muscle from ischemia–reperfusion injury. In this model, BB can enhance the activity of catalase (CAT), glutathione peroxidase, and SOD, and reduce nicotinamide adenine dinucleotide phosphate oxidase activity and F2‐isoprostane and MDA levels.…”
Section: Pharmacological Effects Of Bbmentioning
confidence: 99%
“…Moreover, when oxidative stress or inflammatory responses occurs, the mitogen-activated protein kinase (MAPK) pathways are activated. Specifically, several studies have described that the activation of p38 and ERK1/2 is involved in the brains of epileptic rats [14,15]. It has also been reported that the iron injection model has been proven to activate the p38 and ERK1/2 pathways [6,7,16].…”
Section: Introductionmentioning
confidence: 99%